Effect of irrigation method and application of NPK fertilizer on some physical properties of soil, growth of quinoa (Chenopodium quinoa Willd) and distribution of roots in the soil (Texas Journal of Agriculture and Biological Sciences, 2022)
The current study was conducted at the Agricultural Research Station, College of Agriculture and Marshes, Dhi-Qar University, during the 2020/2021 season. The aim of this work was to determine the best irrigation method (drip, surface) with NPK fertilizer at levels (0, 50, 100 kg do -1 ) in some physical soil properties and growth indicators of quinoa crop growth and root distribution. The obtained data showed that the application of drip irrigation led to an improvement in the physical properties of the soil, as the bulk density decreased by 58.34%, the total porosity increased by 45.29%, and the saturated water conductivity was 36.71% compared with the irrigation system, which was reflected in the vegetative growth characteristics of the quinoa crop, if the treatment T3 (drip irrigation and 100 kg do-1 NPK fertilizer) was superior and gave the highest plant height, leaf area, number of branches and dry weight compared with the rest of the treatments, while the surface irrigation superiority in the distribution of roots in the soil and the treatment of adding manure and 100 kg do-1 NPK fertilizer..